DESIGN OF ROOF STEEL TRUSSES AND REINFORCED CONCRETE MEDIUM MOMENT RESISTING FRAMES ON PERSIBA BALIKPAPAN FOOTBALL STADIUM - ARIF KINANTOKO, FAUZAN
A civil engineer must have a good capability to do a detail structural design. A good structural design have to fulfill the requirement of strength, stiffness, and stability. To meet those requirements, design of structure which has a specific building functions in every locations have their own challenges. In Indonesia, the challenge is how to build an earthquake resistant structure because Indonesia is located in the area where the frequency of earthquakes are high. This paper explains about structural design of earthquake-resistant Stadium which is quite massive and has some special characteristics. The structural design itself is based on architectÃ‚Â’s drawing. To make the earthquake-resistant structure, the stadium will be designed using Medium Moment Resisting Frames (SRPMM). The design process of the stadium will based on earthquake resistance code such as SNI 1726:2012 and building design code such as SNI 1727:2013, SNI 2847:2013 and SNI 1729:2015. The scope of design is centered to reinforced concrete structure and steel truss structure. The detailed design of structural elements are based on structural modelling and analysis using SAP2000 v19 software. In addition, another design software such as SAFE2016 and PCAColumn will be needed. The structural element must be able to hold forces that derived from dead load, superimposed dead load, live load, and earthquake load.